640 QRS INDEX TO PREDICT CARDIAC RESYNCHRONIZATION THERAPY RESPONSE: A TRICENTRIC STUDY. (15th December 2022) - Madaudo, Cristina; Prezioso, Amedeo; Bonni´, Enrico; Mascioli, Giosuè; Pecora, Domenico; Ciaramitaro, Gianfranco; La Greca, Carmelo; Zanchi, Simone; Cuccia, Claudio; Novo, Giuseppina; Corrado, Egle; Coppola, Giuseppe; et al.
Abstract: Background: Several studies have evaluated the role of QRS duration (QRSd) or QRS narrowing as predictor of response to cardiac resynchronization therapy (CRT) in order to reduce non-responders. However, their results have been conflicting. In our study we analyzed retrospectively a cohort of patients from three centers to better correlate the association between the relative change in QRS narrowing index (QI) and clinical outcome and prognosis in patients who underwent CRT implantation. Methods: We included 398 patients in whom a CRT device was implanted in accordance with current guidelines in our three centres. Baseline clinical variables, echocardiographic parameters and pharmacological therapies were included. QRS duration before and after CRT implantation and QI [(pre implant QRS duration - QRS duration during CRT)/pre implant QRS duration × 100] were measured. Results: Respect to echocardiographic follow up at 6 months, a significant improvement in all parameters (EF, LVEDV, LVESV) was observed. In 68% of patients, LVESV decreased by 10% or more. QI was significantly related to reverse remodelling (r = + 0.22; 95% CI: 0.11 to 0.32, p = 0.001). The cut-off value of QI that predicted best LV reverse remodelling after 6 months of CRT was 12.25% (sensitivity 65, 49%, specificity 75%, area under the curve 0.7, p = 0.001). Regarding clinical outcomes at 12 mounths, a statistically significant difference was found between patients with a QI ≤ 12.25%, and those with a QI > 12.25%, in terms of NYHA class worsening (p 0, 04). Another statistically significant difference was found analyzing the relation between QI and the causes of deaths, the mean of the QI of patients who died from cardiovascular causes was lower than patients who died of other causes. (p 0, 0179). Conclusions: Therefore decrease in QRSd after CRT initiation was related to greater echocardiographic reverse remodelling and better outcome from death or cardiovascular hospitalization. Even if larger studies are needed, QI seems to be an easy-to- measure variable that could be used or evaluated to predict CRT response.